Development Of Android-Based PAKIS Learning Media In Class X TKJ History Learning - Sukarto, Muhammad Nur Khalif; Ferdiansyah, Handy; Syamsunir, Syamsunir (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
Development research that aims to develop android-based PAKIS learning media products using the type of Research and Development (R&D) research with the ADDIE development model which includes five stages, namely: (1) Analysis including competency analysis, characteristic analysis, and material analysis; (2) Design including Flowchart and Storyboard Creation; (3) Development including product development, media validation, and product revision; (4) Implementation including product trials; (5) Evaluation including formative evaluation and summative evaluation. The data collection technique uses observation, interviews, documentation, questionnaires, and tests, then the approach used is mixed methods. The results showed that (1) the media validation results were 87% (very valid), (2) the material validation results were 100% (very valid), (3) the teacher response questionnaire assessment results were 90% (very practical), (4) the student response questionnaire results were 93% (very practical), and (5) the N-gain score results were 78 (effective). Based on these data, it can be concluded that PAKIS learning media can be used in the History learning process in class X TKJ SMK Negeri 1 SIDRAP.